High sensitivity tests of the Pauli Exclusion Principle with VIP2. (July 2015) - Marton, J; Bartalucci, S; Bertolucci, S; Berucci, C; Bragadireanu, M; Cargnelli, M; Curceanu, C; Clozza, A; Matteo, S Di; Egger, J-P; Guaraldo, C; Iliescu, M; et al.
Abstract: The Pauli Exclusion Principle is one of the most fundamental rules of nature and represents a pillar of modern physics. According to many observations the Pauli Exclusion Principle must be extremely well fulfilled. Nevertheless, numerous experimental investigations were performed to search for a small violation of this principle. The VIP experiment at the Gran Sasso underground laboratory searched for Pauli-forbidden X-ray transitions in copper atoms using the Ramberg-Snow method and obtained the best limit so far. The follow-up experiment VIP2 is designed to reach even higher sensitivity. It aims to improve the limit by VIP by orders of magnitude. The experimental method, comparison of different PEP tests based on different assumptions and the developments for VIP2 are presented.